Pengaruh Bencana Alam terhadap PDRB Provinsi di Indonesia: Pendekatan Model Pertumbuhan Solow-Swan - Wariyanti, Nur Janah; Rahmayani, Dwi (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Natural disasters are a problem for a country’s economy. This research aims to analyze the influence of natural disasters, Gross Fixed Capital Formation (GFCF), Human Development Index (HDI), and Labor Force Participation Rate (LFPR) on the Gross Regional Domestic Product (GRDP) of 31 Provinces in Indonesia from 2011 to 2023. Research method uses panel data regression with Fixed Effect Model estimation. The results of this research show that GFCF and HDI can increase value GRDP in Indonesia. LFPR does not have a significant effect in a positive direction on GRDP in Indonesia and natural disasters do not have a significant effect in a negative direction.